Is the Revised National Tuberculosis Control Programme achieving early initiation of treatment post two decades of its operation?: A cross-sectional study from Uttarakhand, India - Nautiyal, Ram Gopal; Singh, Rajesh Kumar; Mittal, Sneha; Awasthi, Sadhana (Indian Journal of Community Health, 2019)
Background: Early case finding and prompt initiation of treatment of pulmonary Tuberculosis (PTB) is the most effective strategy to achieve successful TB control. In order to achieve early initiation of treatment, the Revised National TB Control Programme (RNTCP) since its launch in 1997 has been using advocacy, communication and social mobilization (ACSM) strategy targeted at health care providers (HCP) and other stake holders by large scale utilization of electronic and print media. Objective: To study whether RNTCP is really achieving early initiation of TB treatment among infectious PTB patients. Methods: A cross- sectional study among new smear positive PTB patients at Haldwani block of Nainital district of Uttarakhand State of North India. Data was analyzed using the software Epi Info version 7.2.0.1. Results: Of the 85 infectious PTB patients included in the study, the median time consumed between onset of cough and contact with the first HCP, between first HCP contact to confirmation of diagnosis, and between confirmation of diagnosis to initiation of treatment were 6 days, 43 days and 6 days respectively. Overall, median time consumed between onset of cough to initiation of treatment was 61 days. HCPs working in the public health settings fared no better than those in the private health sector in this regard. Conclusions: Although majority patients sought medical care timely, a considerably unacceptable long time was consumed by HCPs in initiation of treatment of PTB.